The correlation of the fecal microbiome with the biochemical profile during menopause: a Brazilian cohort study - Thayane Christine Alves da Silva; Jennefer Aparecida dos Santos Gonçalves; Laura Alves Cota e Souza; Angélica Alves Lima; R. Guerra-Sá (BMC, 2022)
Abstract Background Hormonal, biochemical, and metabolic changes after menopause may alter the quality of life of women, leading to vasomotor, psychological, and genitourinary symptoms, and changes in their gut microbiota, which regulates estrogen levels through the estroboloma. Fecal samples were used to investigate the changes in the gut microbiota during aging and hormonal changes in women. A balanced gut microbiota has been associated with health or disease conditions and remains poorly understood after menopause. This study identified the fecal microbiota, and their association with biochemical and hormonal parameters of a cohort of women in the climacteric in the city of Ouro Preto-MG, Brazil. Methods A total of 102 women aged 40 to 65 years old were recruited and distributed into three groups according to the STRAW criteria for reproductive stage: reproductive (n = 18), premenopausal (n = 26), and postmenopausal (n = 58). Blood samples were collected to measure their serum biochemical and hormone levels, and the participants answered a questionnaire. The gut microbiota was analyzed from fecal samples by qPCR using the genera Bifidobacterium, Bacteroides, Lactobacillus, and Clostridium. Results The following parameters showed differences among the groups: total cholesterol, triglycerides, VLDL, ApoB, urea, calcium, uric acid, and alkaline phosphatase (p < 0.05). qPCR revealed the genus Clostridium to be the most abundant in all three groups. In the reproductive age group, the significant correlations were: Bacteroides with glucose (r = -0.573 p = 0.0129), and SDHEA (r = -0.583 p = 0.0111). For the premenopausal group, they were: Bifidobacteria with total cholesterol (r = 0.396 p = 0.0451), LDL (r = 0.393 p = 0.0468), ApoB (r = 0.411 p = 0.0368); Lactobacillus and calcium (r = 0.443 p = 0.0232), ALP (r = 0.543 p = 0.0041), LPa (r =-0.442 p = 0.02336); and Bacteroides and urea (r =-0.461 p = 0.0176). In the postmenopausal group, they were Bifidobacterium and ALP (r =-0.315 p = 0.0159), Lactobacillus and urea (r =-0.276 p = 0.0356), and Clostridium and beta estradiol (r =-0.355 p = 0.0062). Conclusion In conclusion, the hormonal and metabolic changes during menopause in the population studied were accompanied by a significant change in the fecal microbiota, especially of the genus Clostridium.